A Natural Resource and Landscape Management Framework for the Bergrivier Municipality - Petersen, Aa-ishah Ashaakierah (School of Architecture, Planning and Geomatics, 2014)
Natural resource management formed out of a century long process within regional planning. Early authors such as Mumford, Geddes and Leopold have contributed to this evolution. These early proponents of sustainable natural resource management promoted the relationship between the natural world and human beings. They believed that people were on a negative development path; one that would cause great difficulties in future. Today we see the great negative impacts on the natural environment. Human beings have caused large scale destruction of ecological infrastructure and degradation of land, soils, water and the relationship between people and the natural world. Drawing on past regional theory, this Natural Resource and Landscape Management Framework investigates ways in which to improve the relationship between people and the environment. It does this by employing a Bioregional Framework to investigate the Bergrivier Municipality in the Western Cape, South Africa. This framework investigates the region within its natural context and finds several negative anthropogenic impacts such as low water quality, institutional problems such as low municipal capacity and several positive points to arise, such as the various culturally significant sites and artefacts. The outcomes informed the framework development, a set of spatialised strategies that aim to improve the natural setting of the Bergrivier Municipality and its functioning within the region. The Bioregional Approach provided a holistic framework from which to analyse the study region and sets the stage for well-rounded, considerate policy production.